Autonomous vehicles and risk management for critical traffic situations - Oravský, Daniel; Novák, Richard, 1973-; Luc, Ladislav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This thesis aims to describe, assess, and manage the risks for critical traffic situations associated with the deployment of autonomous vehicles (AVs), touching on the application of insights from Information and Communication Technology (ICT) process and risk management. The study will explore the ethics of autonomous vehicles to evaluate the impact of traffic collision situations. Furthermore, quantitative research will be conducted to investigate respondents' attitudes towards the risk of the described traffic situations associated with AV deployment.
Vedoucí práce: Richard Antonín Novák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses